2016
DOI: 10.1093/jrr/rrw009
|View full text |Cite
|
Sign up to set email alerts
|

The complexity of microRNAs in human cancer

Abstract: MicroRNAs (miRNAs) are small non-coding RNA molecules that have key regulatory roles in cancer, acting as both oncogenes and tumor suppressors. Due to the potential roles of miRNAs in improving cancer prognostic, predictive, diagnostic and therapeutic approaches, they have become an area of intense research focus in recent years. MiRNAs harbor attractive features allowing for translation to the clinical world, such as relatively simple extraction methods, resistance to molecular degradation, and ability to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 39 publications
0
35
0
2
Order By: Relevance
“…MicroRNAs (miRNAs) are small ncRNAs with a length of 22 nucleotides, and their expression is closely related to cancer progression. 13 MiRNAs-targeted therapy technology has developed new strategies for cancer treatment. 14 With the deepening of the research on circRNAs mechanism, it has been found that circRNAs can act as complementary RNAs (ceRNAs) to participate in the regulation of target genes of miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small ncRNAs with a length of 22 nucleotides, and their expression is closely related to cancer progression. 13 MiRNAs-targeted therapy technology has developed new strategies for cancer treatment. 14 With the deepening of the research on circRNAs mechanism, it has been found that circRNAs can act as complementary RNAs (ceRNAs) to participate in the regulation of target genes of miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs), a group of noncoding, small RNA molecules, negatively regulate gene expression via directly interacting with the 3′‐UTR of target gene . MiRNAs regulate many biological roles including cell differentiation, apoptosis, proliferation, cycle, invasion, migration, metastasis, and cell death . Increasing studies demonstrated that miRNA was aberrantly expressed in several tumors such as gastric cancer, bladder cancer, breast cancer, pancreatic cancer, and laryngeal squamous cell carcinoma .…”
Section: Introductionmentioning
confidence: 99%
“… 2 A number of single miRNA biomarkers are associated with the clinical outcome of NSCLC, 3 , 4 and recent reports suggest that various signatures comprising multiple miRNA biomarkers may be more powerful in classifying cancer subtypes than single miRNAs. 5 Nevertheless, the diagnostic efficiency of these miRNA signatures could not be replicated in additional separate patient cohorts. 6 …”
Section: Introductionmentioning
confidence: 99%